Bistability versus metastability in driven dissipative rydberg gases - Letscher, F.; Thomas, O.; Niederprm, T.; Fleischhauer, Michael; Ott, Herwig (Physical Review X, 2017)
We investigate the possibility of a bistable phase in an open many-body system. To this end, we discuss the microscopic dynamics of a continuously off-resonantly driven Rydberg lattice gas in the regime of strong decoherence. Our experimental results reveal a prolongation of the temporal correlations exceeding the lifetime of a single Rydberg excitation and show strong evidence for the formation of finite-sized Rydberg excitation clusters in the steady state. We simulate the dynamics of the system using a simplified and a full many-body rate-equation model. The results are compatiblewith the formation ofmetastable states associated with a bimodal counting distribution as well as dynamic hysteresis. However, a scaling analysis reveals that the correlation times remain finite for all relevant system parameters, which suggests the formation of many small Rydberg clusters and finite correlation lengths of Rydberg excitations. These results constitute strong evidence against the presence of a global bistable phase previously suggested to exist in this system.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Atomic and molecular physics